Advances in three‐dimensional super‐resolution nanoscopy. Issue 10 (13th July 2016) - Zeng, Zhiping; Xi, Peng
Abstract: Three‐dimensional optical super‐resolution imaging is capable of providing 3D visualization of cellular structures in nanoscale detail. The past decade has witnessed the blossoming of 3D super‐resolution imaging technologies. In this review, we comprehensively discuss and compare the imaging depth, resolution enhancement, and imaging speed of the existing 3D super‐resolution imaging techniques.